Intestinal barrier dysfunction in a randomized trial of a specific probiotic composition in acute pancreatitis. - Besselink, MG; van Santvoort, H; Renooij, W; de Smet, M; Boermeester, M; Fischer, K; Timmerman, H; Ahmed Ali, U; Cirkel, G; Bollen, T; van Ramshorst, B; Schaapherder, A; et al. (2009)
OBJECTIVES: To determine the relation between intestinal barrier dysfunction, bacterial translocation, and clinical outcome in patients with predicted severe acute pancreatitis and the influence of probiotics on these processes. SUMMARY OF BACKGROUND DATA: Randomized, placebo-controlled, multicenter trial on probiotic prophylaxis (Ecologic 641) in patients with predicted severe acute pancreatitis (PROPATRIA). METHODS: Excretion of intestinal fatty acid binding protein (IFABP, a parameter for enterocyte damage), recovery of polyethylene glycols (PEGs, a parameter for intestinal permeability), and excretion of nitric oxide (NOx, a parameter for bacterial translocation) were assessed in urine of 141 patients collected 24 to 48 h after start of probiotic or placebo treatment and 7 days thereafter. RESULTS: IFABP concentrations in the first 72 hours were higher in patients who developed bacteremia (P = 0.03), infected necrosis (P = 0.01), and organ failure (P = 0.008). PEG recovery was higher in patients who developed bacteremia (PEG 4000, P = 0.001), organ failure (PEG 4000, P < 0.0001), or died (PEG 4000, P = 0.009). Probiotic prophylaxis was associated with an increase in IFABP (median 362 vs. 199 pg/mL; P = 0.02), most evidently in patients with organ failure (P = 0.001), and did not influence intestinal permeability. Overall, probiotics decreased NOx (P = 0.05) but, in patients with organ failure, increased NOx (P = 0.001). CONCLUSIONS: Bacteremia, infected necrosis, organ failure, and mortality were all associated with intestinal barrier dysfunction early in the course of acute pancreatitis. Overall, prophylaxis with this specific combination of probiotic strains reduced bacterial translocation, but was associated with increased bacterial translocation and enterocyte damage in patients with organ failure.